Hubungan Pengetahuan dan Pemakaian Alat Pelindung Diri dengan Kejadian Dermatitis Kontak pada Penyemprot Pestisida - Annes Waren; Ratih Ayunigtiyas; Tyagita Widya Sari; Aradana Wahyuda (Jurnal Kesehatan Komunitas, 2020)
Taylor et al., 2008 reported that 80% of occupational dermatoses were contact dermatitis. One of the chemicals that can cause skin disorders is pesticides that are often used in the community, especially oil palm plantation companies (PKS). The use of personal protective equipment (PPE) is one risk control for contact dermatitis in workers. This study aims to determine the relationship between the level of knowledge and behavior of PPE usage with contact dermatitis in oil palm pesticide workers. The research design used was cross-sectional using a total sampling technique that is all workers giving oil palm pesticides in one PKS company in a district of 37 people. The variables used were contact dermatitis obtained from workers' medical records, knowledge using questionnaire instruments, and PPE usage behavior through observation for 3 days with random time. The results showed that 62.2% of workers giving oil pesticides had contact dermatitis, there was a significant relationship between the knowledge of the use of PPE and contact dermatitis (p value = 0.001) and there was a significant relationship between the behavior of PPE use with contact dermatitis (p value = 0,000) giver of palm pesticides. To reduce the occurrence of contact dermatitis can be done by increasing the knowledge and behavior of using PPE. Keywords : Contact dermatitis, pesticide, personnel protective equipment, palm oil